A HUMAN RESOURCE COMPETENCY MODEL IN AN EFFORT TO DEVELOP COOPERATIVE PERFORMANCE - Suratman, Maman; Febrianti, Adjeng; Hermina, Nurul (Jurnal Riset Bisnis dan Manajemen, 2025)
In the national economic system, cooperatives have a strategic role in the creation of an advanced, just, and prosperous society based on Pancasila and the 1945 Constitution. Despite their development, the performance of cooperatives has apparently not met expectations. The competency and motivation of human resources are seen as being ineffective, which makes it necessary to find a model that is able to foster better performance. The purpose of this study is to describe a human resource competency model in an effort to develop the performance of cooperatives. The method used in this research is a survey, which is part of a quantitative approach. The source of primary data is the survey’s respondents, while secondary data are drawn from records, books, regulations, and reports. The data collection was carried out using observations, interviews, questionnaires, and through a study of the documentation. A sample of 65 respondents was selected using simple random sampling of a population of 185 managers of cooperatives in West Java. For data analysis, the multiple linear regression technique was used. According to the study’s results, human resource competency and motivation have a significant effect on the performance of cooperatives, both partially and simultaneously, meaning that the more effective the competency and motivation, the higher the quality of the cooperatives’ performance.